Programa Padlet para mejorar la coordinación de actividades académicas en docentes de la I.E.I.P.S.M. N° 601491 Madre Teresa de Calcuta, Iquitos – 2023 - Teagua Lomas, Consuelito (2024)
The objective of the study was to evaluate the effect of the Padlet program in the coordination of academic activities with teachers of the I.E.I.P.S.M. N° 601491 Madre Teresa de Calcuta, Iquitos in the year 2023, thus studying the effectiveness of the program to be tested with the teachers of the I. E.I.P.S.M. N° 601491 Madre Teresa de Calcuta which were a total of 82 and the sample was worked at 100%, it was experimental and its design was pre-experimental (pre-test and post-test with a single group). Using the survey technique and the questionnaire as an instrument, which was subjected to validity testing by means of expert judgment and a reliability test, applying a pilot test to use the cronbach's alpha reliability coefficient, giving positive results for its execution. The results of the contrastation of the general hypothesis where the p-value = 0.000 < 0.05; allowed to accept the general hypothesis "The Padlet program has a positive effect on the coordination of academic activities with teachers of the I.E.I.P.S.M. N° 601491 Madre Teresa de Calcuta, Iquitos - 2023.", concluding that the use of the Padlet program improves the coordination of academic activities among teachers.